The translator a tribesman's memoir of Darfur - Hari, Daoud (New York : Random House, 2008)
This is a harrowing memoir of how one person has made a difference: Daoud Hari helped inform the world about the genocide in Darfur. Hari, a Zaghawa tribesman, grew up in a village in the Darfur region of Sudan. In 2003, traditional life was shattered when government-backed militias attacked Darfur's villages with helicopters and on horseback, raping and murdering citizens and burning villages. His family dispersed, Hari escaped. He and friends helped survivors find food, water, and safety. When international aid groups and reporters arrived, Hari offered his services as a translator and guide, using his high school knowledge of languages. In doing so, time and again he risked his life, for the government of Sudan had outlawed journalists in the region. Then, inevitably, his luck ran out and he was captured. Now freed, he is a living witness to genocide.--From publisher description.
A call from the road -- We are here -- The dead Nile -- A bad time to go home -- My sister's village -- The end of the world -- Homecoming -- The seven of us -- The translator -- Sticks for shade -- Two and a half million stories -- Connections -- Nicholas Kristof and Ann Curry reporting -- Once more home -- Waking up in N'Djamena -- A strange forest -- The sixth trip -- What can change in twenty-four hours? -- Some boys up ahead with a Kalashnikov -- Our bad situation gets a little worse -- Blindfolds, please -- We came to rescue you guys -- We can't think of anything to say -- The rules of hospitality -- Open house at the torture center -- The Hawalya -- My one percent chance.
Keywords: Hari, Daoud; Translators -- Sudan -- Darfur -- Biography; Sudan -- History -- Darfur Conflict, 2003- -- Personal narratives, Sudanese